Method for repairing corroded galvanized steel material
By coating the epoxy resin surface anticorrosion layer with carbon quantum dot reactant on the surface of the galvanized steel material, the problem of poor corrosion resistance of the surface layer after repair of galvanized steel material in the prior art is solved, and the high corrosion resistance repair effect is achieved, which is suitable for the repair of galvanized steel and other metal materials.
Patent Information
- Application Number
- CN202411819052.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-29
AI Technical Summary
After repairing corrosion of galvanized steel materials, the surface layer has poor corrosion resistance, high cost and difficult construction, and cannot meet the corrosion protection requirements within a 40-year life cycle.
Carbon quantum dot reactant that is evenly mixed with carbon quantum dots, zinc powder and styrene, is used to coat the anti-corrosion layer on the epoxy resin surface by cleaning the surface of the galvanized steel material after decontamination, and dry it at 50-70°C to repair the corrosion surface.
It realizes rapid and accurate repair of the corrosion surface of galvanized steel materials, forming a high corrosion-resistant surface, which is suitable for the repair of galvanized steel materials, and is promoted and applied to the restoration research of other metal materials and alloys, extending the service life of the material.
Smart Images

Figure BDA0005182639170000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material repair, and in particular relates to a method for repairing corroded galvanized steel material. Background Art
[0002] The grounding grid device of the substation is laid underground in a harsh environment. It is affected by chemical corrosion of the soil by stray current, electrochemical corrosion, discharge of operating equipment and lightning leakage current, which can easily cause some power grid grounding materials to corrode seriously in a very short time. In severe cases, perforation rupture occurs, leading to power safety accidents. With the development of demand and technology, power grid grounding materials are becoming more and more diversified, and a series of new grounding alloy materials such as zinc-clad steel, copper-clad steel and conductive anti-corrosion coated steel have emerged. However, during the service process, due to different environmental media, under the action of external loads, they will be corroded to varying degrees, which not only affects the appearance of the above-mentioned components, but also seriously affects the service life of the grounding materials. Therefore, timely repair of the damaged galvanized anti-corrosion layer can significantly increase the service life of the metal components of the grounding material, which is very important to ensure the safe operation of the components.
[0003] At present, the main methods for repairing the corrosion and damage on the surface of galvanized steel of grounding materials are spraying zinc-rich paint repair method and thermal spraying zinc repair method. However, when spraying zinc-rich paint to repair the corroded surface, the adhesion of the paint itself is not high. After adding a large amount of zinc powder, the adhesion of the paint is reduced, and the surface is easy to fall off, resulting in poor corrosion resistance of the repaired surface. The use of thermal spraying zinc to repair the corroded alloy surface requires special supersonic spraying equipment, which results in high cost and construction difficulties. At the same time, the reheating of the thermal spraying is also likely to cause the original galvanized layer to be damaged by heat. These shortcomings make the galvanized layer repaired by the above two methods unable to meet the anti-corrosion requirements within the 40-year life cycle of the component. It is urgent to develop a coating for the corroded surface of galvanized steel that is both highly corrosion-resistant and convenient and a preparation method thereof to solve the above problems. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for repairing corroded galvanized steel materials.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for repairing corroded galvanized steel material, characterized in that: comprising:
[0008] Clean and decontaminate the corroded galvanized steel material;
[0009] Evenly mixing carbon quantum dots, zinc powder and styrene to obtain a carbon quantum dot reactant;
[0010] The surface of the galvanized steel material after cleaning and decontamination is coated with a carbon quantum reactant to obtain an epoxy resin surface anti-corrosion layer, which is then dried for repair.
[0011] As a preferred embodiment of the method of the present invention, the cleaning and decontamination treatment is to prepare a decontamination solution, clean and degrease the corroded galvanized steel material in the decontamination solution, and then pickle and wash with water, and dry it.
[0012] As a preferred embodiment of the method of the present invention, the decontamination solution includes one or more of toluene, xylene, ethyl acetate and ethanol.
[0013] As a preferred embodiment of the method of the present invention, the pickling is performed by rinsing with a hydrochloric acid solution, and the number of rinsing times is 1 to 2 times.
[0014] As a preferred embodiment of the method of the present invention, the water washing is performed by washing with running cold water for more than 2 minutes, and then washing with deionized water for more than 2 minutes.
[0015] As a preferred embodiment of the method of the present invention, the carbon quantum dots include one or more of pure carbon quantum dots, nitrogen-doped carbon quantum dots, and sulfur-nitrogen-doped carbon quantum dots.
[0016] As a preferred embodiment of the method of the present invention, the mass ratio of the quantum dots, zinc powder and styrene is 1-2:5:10-12.
[0017] As a preferred embodiment of the method of the present invention, the drying temperature is 50-70°C.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide an epoxy resin surface anti-corrosion layer prepared by a method for repairing corroded galvanized steel materials.
[0019] The epoxy resin surface anti-corrosion layer has a weight loss area of 2.13 to 2.29 mg / mm 2 , the corrosion rate is 5.80×10 -5 ~5.97×10 -5 mg / mm 2 ·h.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention can quickly repair the corroded surface of galvanized steel materials by coating a coating containing carbon quantum dots. Combined with the salt spray test method, the repaired galvanized steel surface can be accurately characterized, and the repair effect of the galvanized steel material can be quickly and accurately determined.
[0022] (2) The present invention adopts a standardized sample preparation and repair process, including the steps of sample cutting, grinding, polishing, cleaning and preparation of repair agents, which is simple to operate and easy to implement; nitrogen-doped or sulfur-nitrogen-doped carbon quantum dot modifiers are designed for different carbon quantum dots. By selecting different carbon quantum dots for parallel experiments, the repair effect of galvanized steel can be more comprehensively evaluated; it is not only suitable for post-corrosion repair of galvanized steel materials, but can also be promoted and applied to the repair research of other metal materials and alloys. It is of great significance to extend the life of key engineering materials such as substation grounding grids, and can effectively ensure the safe and economical operation of power equipment. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0026] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.
[0027] Table 1
[0028] name Commercial channels Part Number Xylene Sinopharm Chemical Reagent Co., Ltd. 10023428 Ethanol Sinopharm Chemical Reagent Co., Ltd. 14057 Sodium hydroxide Sinopharm Chemical Reagent Co., Ltd. 14958 Acetaldehyde Sinopharm Chemical Reagent Co., Ltd. 40083766 Concentrated hydrochloric acid Sinopharm Chemical Reagent Co., Ltd. - o-Phenylenediamine Sinopharm Chemical Reagent Co., Ltd. 80099826 Thiourea Sinopharm Chemical Reagent Co., Ltd. 10022318 Urea Sinopharm Chemical Reagent Co., Ltd. - Zinc powder - -
[0029] Example 1
[0030] (1) Clean and decontaminate the galvanized steel sheet; use cotton yarn, soft cloth or brush dipped in xylene solvent to clean the oil stains on the surface of the galvanized steel sheet, then clean it with ethanol, and wait for the solvent on the surface of the galvanized steel sheet to evaporate and set aside;
[0031] The galvanized steel sheet that has been degreased by solvent was rinsed twice in a 5wt% hydrochloric acid solution, then rinsed in running cold water for 3 minutes, and then rinsed in deionized water for 3 minutes, and then dried for use.
[0032] (2) Slowly add 20 g of sodium hydroxide into a beaker containing 100 mL of acetaldehyde, stir evenly at room temperature for 2 h, then add 3 mL of concentrated hydrochloric acid into the beaker, and continue stirring for 3 h until the reaction is complete;
[0033] After the reaction is completed, the lower layer solution is filtered and dialyzed for 48 hours using a dialysis bag with a molecular weight cutoff of 1000, and the water is changed every 3 hours to remove the unreacted reactants to achieve the purpose of purification. Finally, the dialyzed solution is placed in a blast furnace at 65°C and dried for 7 hours to obtain pure carbon quantum dots in a dark brown powder with a high yield;
[0034] Pure carbon quantum dots, zinc powder (600 mesh first-grade zinc powder) and styrene were uniformly mixed in a mass ratio of 1:5:10 to obtain a carbon quantum dot reactant.
[0035] (3) coating the epoxy resin surface with a carbon quantum dot reactant to obtain a first coated surface; coating the first coated surface with a carbon quantum dot reactant again to obtain a second coated surface; cleaning the second coated surface with an epoxy resin brush, and drying at 60° C. to obtain an epoxy resin surface anti-corrosion layer with a carbon quantum dot reactant embedded on the surface of the galvanized steel material.
[0036] Example 2
[0037] (1) Use cotton yarn, soft cloth or brush dipped in toluene solution to clean the oil stains on the surface of the galvanized steel sheet, and then use a mixed solution prepared with ethanol and ethyl acetate in a mass ratio of 1:1 to clean it. After the solvent on the surface of the galvanized steel sheet evaporates, it is ready for use;
[0038] The galvanized steel sheet that has been degreased by solvent was rinsed twice in a 5wt% hydrochloric acid solution, then rinsed in running cold water for 3 minutes, and then rinsed in deionized water for 3 minutes, and then dried for use.
[0039] (2) At room temperature, 4 g of o-phenylenediamine was dissolved in 40 mL of 40% acetaldehyde, and 12 g of NaOH was slowly added into the solution in four portions and stirred at a constant speed for 2 days. During the stirring process, 6 mL of 10 wt% dilute hydrochloric acid and deionized water were added. After the stirring was completed, the lower layer of solution was filtered and purified by dialysis with an MD34 dialysis bag with a molecular weight cutoff of 2000 to remove unreacted small molecule compounds. The water was changed every 3 hours for 48 hours. Finally, the dialyzed and purified liquid was placed in a freeze dryer and dried for 2 days to obtain dark brown solid powder of nitrogen-doped pure carbon quantum dots;
[0040] The nitrogen-doped carbon quantum dots, zinc powder and styrene were uniformly mixed in a mass ratio of 2:5:12 to obtain a carbon quantum dot reactant.
[0041] (3) coating the epoxy resin surface with a carbon quantum dot reactant to obtain a first coated surface; coating the first coated surface with a carbon quantum dot reactant again to obtain a second coated surface; cleaning the second coated surface with an epoxy resin brush; and drying at 0° C. to obtain an epoxy resin surface anti-corrosion layer with a carbon quantum dot reactant embedded on the surface of the galvanized steel alloy.
[0042] Example 3
[0043] (1) Use cotton yarn, soft cloth or brush dipped in toluene solution to clean the oil stains on the surface of the galvanized steel sheet, then clean it with ethyl acetate, and wait for the solvent on the surface of the galvanized steel sheet to evaporate and set aside;
[0044] The galvanized steel sheet that has been degreased by solvent was rinsed once in a 5wt% hydrochloric acid solution, then rinsed in running cold water for 4 minutes, and then rinsed in deionized water for 3 minutes, and then dried for use.
[0045] (2) At room temperature, 4 g of thiourea and 4 g of urea were dissolved in 40 mL of 40% acetaldehyde, and then 12 g of NaOH was slowly added. The reaction was completed after stirring for 2 days. During the process, 6 mL of 10% dilute hydrochloric acid and 100 mL of deionized water were added. After the reaction was completed, the lower layer of the solution was obtained by filtration. Dialysis was performed for 24 hours using a dialysis bag with a molecular weight cutoff of 1000 to remove unreacted small molecules, and the water was replaced every 3 hours. Finally, the purified liquid was freeze-dried in a freeze dryer for 48 hours to obtain dark brown solid powder of sulfur-nitrogen doped pure carbon quantum dots;
[0046] Sulfur and nitrogen doped pure carbon quantum dots, zinc powder (700 mesh) and styrene were uniformly mixed in a mass ratio of 2:5:12 to obtain a carbon quantum dot reactant.
[0047] (3) coating the epoxy resin surface with a carbon quantum dot reactant to obtain a first coated surface; coating the first coated surface with a carbon quantum dot reactant again to obtain a second coated surface; cleaning the second coated surface with an epoxy resin brush; and drying at 0° C. to obtain an epoxy resin surface anti-corrosion layer with a carbon quantum dot reactant embedded on the surface of the galvanized steel alloy.
[0048] Example 4
[0049] (1) Use cotton yarn, soft cloth or brush to dip into a solution of toluene and xylene in a volume ratio of 1:1 to clean the oil stains on the surface of the galvanized steel sheet, then clean it with ethanol, and wait for the solvent on the surface of the galvanized steel sheet to evaporate and set aside;
[0050] The galvanized steel sheet after solvent degreasing was rinsed once in 5wt% hydrochloric acid solution, then rinsed in running cold water for 5 minutes, and then rinsed in deionized water for 3 minutes. It was dried and set aside.
[0051] (2) 4 g of phenylenediamine and 1 g of thiourea were mixed evenly in 60 mL of N,N-dimethylformamide and 20 mL of deionized water. The mixed solution was injected into the reactor and heated at 240 °C for 8 h. After the mixture was cooled to room temperature, it was dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 1000 to remove unreacted small molecules and solvents. Finally, the dialyzate was freeze-dried for 72 h to obtain purple solid sulfur-nitrogen-doped carbon quantum dots.
[0052] The sulfur-nitrogen doped carbon quantum dots, zinc powder and styrene were uniformly mixed in a mass ratio of 2:5:10 to obtain a carbon quantum dot reactant.
[0053] (3) coating the epoxy resin surface with a carbon quantum dot reactant to obtain a first coated surface; coating the first coated surface with the carbon quantum dot reactant again to obtain a second coated surface; cleaning the second coated surface with an epoxy resin brush; and drying at 60° C. to obtain an epoxy resin surface anti-corrosion layer with the carbon quantum dot reactant embedded on the surface of the galvanized steel material.
[0054] Example 5
[0055] (1) Use cotton yarn, soft cloth or brush to dip into a solution of toluene and xylene in a volume ratio of 1:1 to clean the oil stains on the surface of the galvanized steel sheet, then clean it with ethanol, and wait for the solvent on the surface of the galvanized steel sheet to evaporate and set aside;
[0056] The galvanized steel sheet after solvent degreasing was rinsed once in 5wt% hydrochloric acid solution, then rinsed in running cold water for 5 minutes, and then rinsed in deionized water for 3 minutes. It was dried and set aside.
[0057] (2) 4 g of phenylenediamine and 1.5 g of thiourea were mixed evenly in 60 mL of N,N-dimethylformamide and 20 mL of deionized water. The mixture was injected into the reactor and heated at 240 °C for 8 h, and then cooled to room temperature. Then, the mixture was dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 1000 to remove unreacted small molecules and solvents. Finally, the dialyzate was freeze-dried for 72 h to obtain purple solid sulfur-nitrogen-doped carbon quantum dots.
[0058] The sulfur-nitrogen doped carbon quantum dots, zinc powder and styrene were uniformly mixed in a mass ratio of 3:5:10 to obtain a carbon quantum dot reactant.
[0059] (3) coating the epoxy resin surface with a carbon quantum dot reactant to obtain a first coated surface; coating the first coated surface with the carbon quantum dot reactant again to obtain a second coated surface; cleaning the second coated surface with an epoxy resin brush; and drying at 60° C. to obtain an epoxy resin surface anti-corrosion layer with the carbon quantum dot reactant embedded on the surface of the galvanized steel material.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that no carbon quantum dots are added in step (2).
[0062] Example 5
[0063] A 5 wt % sodium chloride salt solution with a pH value of 6.8 was used as the spray solution, and the test temperature was 35° C. The epoxy resin surface anticorrosive layers obtained in Examples 1 to 4 and the comparative example were subjected to a neutral salt spray test. Table 2 is a test result table of the neutral salt spray test for 48 hours.
[0064] Table 2
[0065]
[0066] It can be seen from Comparative Example 1 that the repair agent based on the prepared carbon quantum dots is coated on the corroded galvanized steel material, and has a good corrosion inhibition effect in the neutral salt solution experiment. The repaired galvanized steel can continue to be used as a grounding material. From the results of Examples 1-4, it can also be known that Example 2 is the best example. The combination of pure carbon quantum dots and nitrogen-doped carbon quantum dots and zinc powder will enhance the corrosion inhibition rate of galvanized steel, while sulfur-nitrogen-doped carbon quantum dots will increase the corrosion of galvanized steel within a certain range due to the addition of sulfur elements; from the results of Example 5, it can also be known that when the sulfur content in the additive increases, its corrosiveness increases. In addition, a high concentration of carbon quantum dots will enhance the anti-corrosion effect.
[0067] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for repairing corroded galvanized steel material, characterized in that: include, Clean and decontaminate the corroded galvanized steel material; Evenly mixing carbon quantum dots, zinc powder and styrene to obtain a carbon quantum dot reactant; The surface of the galvanized steel material after cleaning and decontamination is coated with a carbon quantum reactant to obtain an epoxy resin surface anti-corrosion layer, which is then dried for repair.
2. The method according to claim 1, characterized in that: The cleaning and decontamination treatment comprises preparing a decontamination solution, cleaning and degreasing the corroded galvanized steel material in the decontamination solution, and then pickling, washing with water, and drying.
3. The method according to claim 2, characterized in that: The decontamination solution includes one or more of toluene, xylene, ethyl acetate and ethanol.
4. The method according to claim 2, characterized in that: The pickling is performed by washing with a hydrochloric acid solution, and the washing times are 1 to 2 times.
5. The method according to claim 2, characterized in that: The water washing is washing with running cold water for more than 2 minutes, and then washing with deionized water for more than 2 minutes.
6. The method according to claim 1, characterized in that: The carbon quantum dots include one or more of pure carbon quantum dots, nitrogen-doped carbon quantum dots, and sulfur-nitrogen-doped carbon quantum dots.
7. The method according to claim 6, characterized in that: The mass ratio of the quantum dots, zinc powder and styrene is 1-2:5:10-12.
8. The method according to claim 1, characterized in that: The drying temperature is 50-70°C.
9. The epoxy resin surface anticorrosive layer obtained by the method described in claims 1 to 8.
10. The epoxy resin surface anticorrosive layer according to claim 9, characterized in that: The epoxy resin surface anti-corrosion layer has a weight loss area of 2.13 to 2.29 mg / mm 2 , the corrosion rate is 5.80×10 -5 ~5.97×10 -5 mg / mm 2 ·h.